EFFECT OF CHIPPING ON THE SPILLAGE OF YIELD ELEMENTS AND LEAF SURFACE FORMATION IN COTTON - Mamatkulov Orifjon Odiljon ogli; Makhalikov Rozali Bakhtiyor ogli; Kholikov Muhriddin Bakhromjon ogli (Web of Journals Publishing, 2025)
In this article, the shedding of crop elements at different seedling thicknesses in cotton, the factors affecting the shedding, especially the methods of weeding, the effect of climate, agrotechnical factors are explained.
Keywords: Defoliation, pruning, productivity, layer, cone, cob, flower, node, control, mechanical pruning, manual pruning, uniting.